Analisis Pemahaman Pasien Terhadap Hak dan Kewajiban Pasien di Klinik Pratama Kelambir - Sulisna, Aida; Ilham, Muhammad Adiul; Pohan, Hana Dhini Julia (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The rights and obligations of patients are regulated in Law number 36 of 2009 concerning health. Various patient rights include; the right to information, the right to give consent, the right to medical secrets and the right to a second opinion. Meanwhile, the patient's obligation is to provide correct information to the doctor, comply with the doctor's or nurse's recommendations, provide appropriate compensation for services and the patient also has an obligation not to force his wishes to be carried out by the doctor if it is contrary to the freedom and nobility of the doctor's profession. To analyze patient understanding of patient rights and obligations at the Kelambir Pratama Clinic. The method used is quantitative with a cross sectional analytical survey approach. The research population is 82 patients in 2023 and the sample is Total Sampling. Sampling was carried out using the Accidental Sampling method. Show that there is an influence of education with a p-value= 0.000<0.05, an environmental influence with a p-value= 0.000<0.05 and an influence of information sources with a p-value= 0.000<0.05 on the patient's level of understanding. The conclusion is that there is an influence of education, environment and information sources on the level of understanding of patient rights and obligations at the Pratama Klambir Clinic.  Keywords: Understanding Patient Rights and Obligations  ABSTRAK Hak dan kewajiban pasien diatur dalam Undang-Undang nomor 36 tahun 2009 tentang kesehatan. Macam- macam hak pasien meliputi; hak atas infomasi, hak untuk memberikan persetujuan, hak atas rahasia kedokteran dan hak atas pendapat kedua. Sedangkan kewajiban pasien adalah memberikan informasi yang benar kepada dokter, mematuhi anjuran dokter atau perawat, memberi imbalan jasa yang layak dan pasien juga mempunyai kewajiban untuk tidak memaksakan keinginannya agar dilaksanakan oleh dokter apabila berlawanan dengan kebebasan dan keluhuran profesi dokter. Untuk menganalisis Pemahaman Pasien Terhadap Hak dan Kewajiban Pasien Di Klinik Pratama Kelambir. Metode yang digunakan adalah kuantitatif dengan pendekatan survey analitic cross sectional. Populasi penelitian adalah pasien pada tahun 2023 sebanyak 82 pasien dan sampel adalah Total Sampling. Penarikan sampel dilakukan dengan metode Accidental Sampling. Menunjukkan bahwa ada pengaruh pendidikan dengan p-value= 0,000<0,05, pengaruh lingkungan dengan p-value= 0,000<0,05 dan pengaruh sumber informasi dengan p-value= 0,000<0,05 terhadap tingkat pemahaman pasien. Kesimpulan ada pengaruh pendidikan, lingkungan dan sumber informasi terhadap tingkat pemahaman hak dan kewajiban pasien di Klinik Pratama Klambir Kata Kunci: Pemahaman Hak dan Kewajiban Pasien